Systematic literature review: implications of mental illness on life and working integrity - Saleh, Nor Shela; Rosli, Mohd Shafie (2021)
Mental health problems in society are becoming new and more distressing as explained by the Ministry of Health Malaysia and the World Health Organization. Mental problems occur amongst working adults, the elderly, adolescents and children, men and women. Recent research confirms that the causes of mental health problems are due to genetic problems, personal problems, financial problems, learning pressures and stress at workplace. The effects of mental health problems can lead to depression, emotional tension, personality disorder and suicide. In order to obtain a wealth of information, researchers have accompanied critical analysis studies by viewing at several empirically established from previous studies. The first finding shows that mental illness classified as a brain disorder, an emotional disorder and an abnormal attitude. The second finding explains that the level of mental health knowledge among students is still low. The third study examines the causes of schizophrenia, which have four causes of the disease, namely genetic factors, drugs, work stress and poverty. The fourth finding explains the experience of caring for a mentally ill person who is also having trouble in the life of the patient's family. Generally, this study explains that mental illness is a problem that has various negative effects on various people. Implications of mental illness transpire over the long term if treatment not properly performed. Therefore, proactive initiatives prerequisite to be taken by all parties to ensure the quality of life of the people will perfect and normal devoid of interruption of mental illness.